Regulating the Crypto Ecosystem : The Case of Unbacked Crypto Assets - Bains, Parma; Ismail, Arif.; Melo, Fabiana; Sugimoto, Nobuyasu (Washington, D.C. : International Monetary Fund, 2022)
Unbacked crypto assets are the oldest and most popular type of crypto assets, relying not on any backing asset for value but instead on supply and demand. They were originally developed to democratize payments but are mostly used for speculation. Crypto assets were designed to disintermediate financial services, but centralized entities, such as exchanges and wallet providers, offer key functions to users and sustain the necessity of trust in one or several entities. At present, many of these entities are not covered by existing conduct, prudential, or payment regulations and can generate risks to market integrity, market conduct, and potential financial stability. We recommend that global bodies work to develop common taxonomies that can inform global and cross-sectoral standards while improving data insights. Standards should be risk-based, with greater requirements on entities and activities that generate more risk. Crypto asset service providers that deliver core functions and generate key risks should be licensed, registered, or authorized.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Consumer Protection; Foreign Exchange; Informal Economy; Underground Econom